Análise de parâmetros hemocitométricos como preditores de mortalidade em pacientes hospitalizados com covid-19. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The severity of COVID-19 cases is associated with an exacerbated inflammatory response, known as a cytokine storm. A controlled and effective immune response is crucial to eliminating the harmful effects of infection. Several hematological parameters reflect the immune system's state, making monitoring this response possible. However, studies about hemocytometric parameters not used in clinical practice are scarce. Therefore, this study aimed to evaluate the use of hemocytometric parameters as predictors of mortality in hospitalized patients with COVID-19, according to the final outcome (hospital discharge or death) within 30 days. An observational study was carried out, with data from patients with COVID-19 obtained from the laboratory of the Hospital Universitário Regional dos Campos Gerais (HURCG), Ponta Grossa - Paraná, during the period from July to August 2021. Demographic and clinical data were obtained from 230 patients diagnosed with COVID-19. After the selection criteria, 140 patients were included in the study. Blood count parameters, including hemocytometrics: NE-SSC (neutrophil reactivity), NE-SFL (neutrophil metabolic activity), LY-SSC (lymphocyte nucleus irregularity, cytoplasmic granulation, and/or vacuolization) and LY-SFL (lymphocyte metabolism and/or cell membrane permeability), as well as inflammatory markers: CRP, NLR, PLR, LMP were obtained at hospital admission and within 24 hours preceding to the final outcome (discharge or death). Patients were divided into two groups: survivors (n=102) and non-survivors (n=38). Advanced age, comorbidities, and lung involvement >50% were considered risk factors for COVID-19. The parameters NESSC, RDW-CV, NLR, and CRP have been shown to be associated with mortality prognosis. They can be used to assess 30 days survival, with an estimated cut-off point of 153 Ch, 13.2%, 14 and 13, 9 mg/dL, respectively. However, only age was considered an independent risk factor for mortality. In the 24-hour assessment preceding to the final outcome (discharge or death), the changes in the parameters were more expressive, with the worst results being found in the non-survivors group. These results showed that the NE-SSC, RDW-CV, and NLR parameters remained changed until the final outcome. Therefore, the results of the present study can be explored in future studies to develop rule algorithms for clinical prediction in patients with COVID-19.
Keywords: Doença por Coronavírus 2019; Infecção pelo SARS-CoV-2; Testes hematológicos; Biomarcadores; Mortalidade; Coronavirus Disease 2019; SARS-CoV-2 infection; Hematological tests; Biomarkers; Mortality; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA